PENGARUH PENGGUNAAN GAME EDUKASI WORDWALL TERHADAP MINAT DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SIMULASI DIGITAL DI SMK PGRI CIKONENG CIAMIS - seli, seli sayidah; Alfadl, Alfadl Habibie; Taofik, Taofik Muhammad (PRODUKTIF : Jurnal Ilmiah Pendidikan Teknologi Informasi, 2024)
This research was conducted at SMK PGRI Cikoneng Ciamis, with a research focus on class X students with a population of 96 students. The samples of this study were class X OTKP and X AKL which were selected by Non-Probability Sampling. The validation of the interest questionnaire resulted in a score of 23, as well as an average of 4.6, which indicates the reliability of the questionnaire as a measuring tool. The average interest score from the questionnaire was 3.38, classified as “Good Enough”, indicating room for improvement in student engagement. Normality tests confirmed that the learning interest data was normally distributed. A one-sample t-test showed a significant difference in the mean learning interest (74.38) compared to the set value of 65 (t = 3.457, p = 0.001). In terms of learning outcomes, 18 students (17.82%) scored ≥ 90.0 (“Excellent”), and the overall mean score was 85.14 (“Good”). The results of the independent sample t-test showed a significant difference between the experimental class using the Wordwall educational game method (mean = 91.19) and the control class (mean = 78.48), with a value of t = 9.880 and p = 0.000. This study found that the materials and learning methods applied had a positive effect on student interest and learning outcomes, and encouraged the need for further improvement of interesting learning strategies.